ANALYSIS OF STUDENTS' LOGICAL THINKING SKILLS IN COMPUTER PROGRAMMING LEARNING - Asnurul Isroqmi; Allen Marga Retta; Tika Dwi Nopriyanti (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to describe students' logical thinking skills in computer programming learning on algorithmic and programming subjects. The purpose of learning computer programming is to make a program that can do a calculation or